Thickness Dependence of Electrical and Optical Properties of Sol Gel ZnO Coatings - Baraka, Rajai (Asian Journal of Chemistry, 2010)
Single and multilayer transparent conducting zinc oxide film has been prepared on boro silicate substrates by the sol gel dip coating process. Bach layer was kept at 600oC in a conventional fumace for 15 min. The final coatings were then tempered under a flux of forming gas (N2/H2) at 400oC for 2 h. The coatings were characterized by surface stylus profiling, optical spectroscopy (UV, near IR) and combined Hall and van der Pauw techniques. The thickness, sheet resistance, electrical resistivity, mobility and transmittance of obtained ZnO coatings were studied as a function of dipping speeds and the number of coatings. The film resistivity decreases as the number of coatings increases while the carrier mobility increases. The transmittance of ZnO multilayers is slightly decreased with increasing the number of coatings.